2018
DOI: 10.1111/jgs.15604
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Fasting Glucose Increases Risk of Unrecognized Myocardial Infarctions in an Elderly Cohort

Abstract: Background: Up to 45% of initial myocardial infarctions (MI) may be unrecognized (UMI). Diabetes mellitus (DM) is a risk factor for UMI, therefore further investigation of glucose levels as a risk factor for UMI is warranted. Methods: The relationship between glucose levels and UMI was examined in the Cardiovascular Health Study (CHS): a cohort study of individuals aged ≥ 65 years old. Those with prior coronary heart disease (CHD) or a UMI on initial ECG were excluded. The study population consisted of 4,355… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 56 publications
(105 reference statements)
0
6
0
Order By: Relevance
“…Our study showed that those with diabetes mellitus had the significantly longer decision times. Diabetes Mellitus is not only a major risk factor of coronary artery disease, it also results in silent MI [ 35 ] and more atypical symptoms, all of which could contribute to delays in recognizing symptoms, and hence delays in presentation. A large percentage (53.8%) of the patients in our study attributed their symptoms to PUD or acid reflux.…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed that those with diabetes mellitus had the significantly longer decision times. Diabetes Mellitus is not only a major risk factor of coronary artery disease, it also results in silent MI [ 35 ] and more atypical symptoms, all of which could contribute to delays in recognizing symptoms, and hence delays in presentation. A large percentage (53.8%) of the patients in our study attributed their symptoms to PUD or acid reflux.…”
Section: Discussionmentioning
confidence: 99%
“…8 The Cardiovascular Health Study group reported that abnormal fasting glucose increases the risk of unrecognized MI in an older adult cohort. 9 In a study conducted in Iceland, all-cause mortality of unrecognized MI was higher than MI, and unrecognized MI was associated with an elevated risk of nonfatal MI and heart failure. 10 It was reported that individuals who experience unrecognized MI had reduced pain sensitivity compared with people who experienced recognized MI.…”
mentioning
confidence: 97%
“…In addition, in the UK Prospective Diabetes Study, approximately 1 in 6 patients with newly diagnosed type 2 DM had evidence of SMI 8 . The Cardiovascular Health Study group reported that abnormal fasting glucose increases the risk of unrecognized MI in an older adult cohort 9 . In a study conducted in Iceland, all-cause mortality of unrecognized MI was higher than MI, and unrecognized MI was associated with an elevated risk of nonfatal MI and heart failure 10 .…”
mentioning
confidence: 99%
“…In the light of differences in ECG diagnostic criteria and study population, there is wide variability in prevalence estimation for silent MI [15]; however, the prevalence of silent MI may reach up to 6.4% in general populations [16], and being more prevalent among diabetic patients. Moreover, diabetes and prediabetes status could be a predictive and associated factors for silent MI [16,17], but about prediabetes, the relation is less clear and necessitates further studies [18].…”
mentioning
confidence: 99%